Marketing to Bottom-of-the-pyramid consumers in an emerging market: the responses of mainstream consumers - Gupta, Reetika (Journal of business ethics, 2024)
Many companies are now targeting the sizeable segment of consumers in Bottom-of-the-pyramid (BoP) markets with new products to specifically address their needs. As mainstream consumers become aware of these initiatives, their views on what products may be construed as appropriate for BoP marketplaces, may influence their attitudes towards the companies engaging in BoP activities. We propose that when the mainstream consumers are culturally distant from the BoP consumers, they have less favourable attitudes towards a company marketing a hedonic product to BoP consumers, compared to a utilitarian one. However, when the mainstream consumers are culturally closer to the BoP consumers, they are less likely to react negatively to a company's marketing of a hedonic product compared to a utilitarian one. We theorize that these differences in evaluation are based on the mainstream consumers’ expectations regarding the products a company would/should target towards BoP consumers. We also examine two company characteristics (country-of-origin and profit orientation) as contingency factors affecting the attitudes of culturally close mainstream consumers towards companies engaging in BoP practices. Across two studies, we find support for our hypotheses. This research adds to a new stream of scholarship that theorizes about the permissible consumption mindset of mainstream consumers. The research also provides guidance to marketing managers and communication experts to help build favourable company attitudes and minimize any mainstream negativity towards a company's marketing initiatives in the BoP domain.